Creating Ambassadors of Planet Earth: The Overview Effect in K12 Education - van Limpt - Broers, H. Anna T.; Postma, Marie; Louwerse, Max M. (Frontiers in Psychology, 2020)
The Overview Effect is the commonly reported experience of astronauts viewing planet Earth from space, and the subsequent reflection on, and processing of this experience. The Overview Effect is associated with feelings of awe, self-transcendence, and a change of perspective and identity that manifest themselves in taking steps towards protecting the fragile ecosystem. In the current study, we investigated whether the Overview Effect can be obtained in school children when simulated using virtual reality and whether the effect has a positive impact on learning gains. Using questionnaires and attention data in an existing simulation environment used in the school system, we showed that the virtual reality simulation elicits an Overview Effect experience. Moreover, the experience yields learning gains in the domain of astrophysics. These findings are in line with past evidence regarding the positive impact of awe on learning and can be used to support further investigations of the relation between the Overview Effect and behavioral changes, specifically for educational purposes.